Diseases affecting livestock production mediate landscape scale of a changing pasture regime in Lake Mburo Conservation Area, Uganda - Nina, Pius; Mugisha, Samuel; Basuta, Gilbert; Kateregga, Eseza (International Journal of Biological Research, 2014)
This study investigated whether spatial disparities in pastoral herd sizes across rangelands from Lake Mburo National Park (LMNP) boundary was responsible for a changing pasture regime. A midst growing concern that cattle diseases associated with wild ungulates outside the protected areas impose limitations on pastoralist household income, the affected communities respond by overstocking as an adaption to disease risks. Therefore, increasing cattle stock holding among pastoralists living at the park boundary was suspected to be facilitating the disappearance of forests in Lake Mburo Conservation Area (LMCA). We applied ecosystem approach in a cross-sectional survey design to assess whether impact of diseases transmitted at the nexus of wildlife and livestock play intermediary role in the emerging spatial pattern of pasture regimes in LMCA.Â Paired sample t-test was used to examine the mean differences of animal populations between managed and unmanaged pasture and interpreted with Geo-eye satellite data of a typical landscape of savanna ecosystem of LMCA. The results revealed a significant difference (p < 0.05) in the distribution of wild species of animals between managed and unmanaged pasture. Spatial variation in population abundance of wild animals between distance zones was also reflected in the distribution of average household stockholding as well as cattle mortalities along a distance gradient from LMNP boundary. These findings could guide evidence based monitoring of long term effects of changing pasture regimes on pastoralist livelihood systems around LMCA. For example, future research should consider complementarities and overlap of the diets of wild ungulates and cattle at the nexus of wildlife and livestock interface. This will provide an understanding of how wildlife presence in rangelands can lead to either favorable or adverse changes in the fauna as far as the domestic livestock species of cattle and small ruminants are concerned.